2023
DOI: 10.1002/adem.202300025
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Elastic Waveguide Cloak in Thin Plates

Abstract: Vibration in thin plates is a common issue in structural engineering that can significantly impact the performance of structures. One crucial objective is to control vibration intensity. Metamaterials offer a promising solution to this challenge. Herein, a multiband elastic waveguide cloak that uses metamaterials and does not require active components or complex designs is introduced. By converting flexural waves to waveguide‐trapped waves, a cloaking region with negligible vibration can be created. Herein, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Moreover, Liu et al [348] experimentally demonstrated source illusion devices for flexural wave manipulation. Although not explicitly mentioned here, there is other notable research progress on the relevant topic [349][350][351][352][353][354][355][356][357][358].…”
Section: Othersmentioning
confidence: 99%
“…Moreover, Liu et al [348] experimentally demonstrated source illusion devices for flexural wave manipulation. Although not explicitly mentioned here, there is other notable research progress on the relevant topic [349][350][351][352][353][354][355][356][357][358].…”
Section: Othersmentioning
confidence: 99%